ANALYZING THE DEIXIS OF SONG LYRICS ENTITLED “NEW ROMANTICS” BY TAYLOR SWIFT - Siska Sri Astuti; Dasep Suprijadi (PROJECT (Professional Journal of English Education), 2022)
This research is aimed to discover the deixis used in Taylor Swift’s song entitled New Romantics. This study's objectives are 1) to describe the types of deixis used in the lyrics of the song New Romantics by Taylor Swift; 2) to describe the meaning of the deixis reference in the song's lyrics New Romantics by Taylor Swift. A descriptive qualitative is used to investigate the data—the researcher analyzes the data using data tables to generate a better data result. Based on the finding, it was found that three deixes were found in analyzing the song; persona deixis, time deixis, and place deixis. The type of deixis most used in the song lyrics is person deixis, which consisted of 59 data.